Significance of bilayer-forming phospholipids for skeletal muscle insulin sensitivity and mitochondrial function - Grapentine, Sophie (J Biomed Res, 2020)
Phosphatidylcholine (PC) and phosphatidylethanolamine (PE), which make up the bulk of mammalian cell membrane phospholipids, are recognized for their importance in metabolic health. Perturbations in the ratio of PC:PE can affect membrane integrity and function, which thus have serious health consequences. Imbalance in the hepatic PC and PE membrane content can be linked to metabolic disturbances such as ER stress, fatty liver and insulin resistance. Given that impaired insulin sensitivity underlies the pathology of many metabolic disorders and skeletal muscle is a significant regulator of energy metabolism, it is likely that aberrant phospholipid metabolism in skeletal muscle affects whole-body insulin sensitivity. Sarco/endoplasmic reticulum Ca(2+) ATPase (SERCA) activity and mitochondrial function respond to alterations in PC:PE ratio and are associated with glucose homeostasis. Moreover, PC and PE content within the mitochondrial membrane influence mitochondrial respiration and biogenesis and thus, metabolic function. As skeletal muscle phospholipids respond to stimuli such as diet and exercise, understanding the implications of imbalances in PC:PE ratio is of great importance in the face of the rising epidemic of obesity related diseases. This review will summarize the current state of knowledge signifying the links between skeletal muscle PC:PE ratio and insulin sensitivity with respects to PC and PE metabolism, SERCA activity, mitochondrial function and exercise.